Asymmetry of the economic development of the Eurasian Economic Union: analysis and recommendations - A. A. Urunov; A. R. Vagapova; S. I. Shirinova (Вестник университета, 2024)
The article analyses the asymmetry of the development of the Eurasian Economic Union countries (hereinafter referred to as the EAEU). The objective of the work is to analyse the symmetrical development of countries within the framework of the EAEU and to formulate measures and recommendations for increase of the economic potential of the countries. In order to achieve the purpose, the objective of comparative assessment on the basis of three indicators was set and overcome. The three indicators include gross domestic product per capita, investments per capita and average accrued salary. The corresponding calculations were done for each indicator, and graphs were constructed showing the general state of the economic development. During the study, the methods of factor and system analysis were applied. The initial data for the study were the official sources of the statistical authorities of the EAEU countries, the Interstate Statistical Committee of the Commonwealth of Independent States as well as publications and scientific articles related to this topic. The main problem is the uneven economic development of the EAEU member states which leads to negative consequences for strengthening the integration process. As a result of the study, some measures were proposed to achieve the symmetrical development of the countries within the framework of the EAEU, and recommendations were prepared for the effective development of interaction between the member countries of the integration association. Following the results of this work, a conclusion was formulated on strengthening ties between the countries by focusing on a mixed economy with government regulation, infrastructure development and increased investment activity.